Percepção dos agentes comunitários de saúde frente ao risco de infecção da tuberculose - Velez, Yushiara Emily Vargas (2013)
Tuberculosis is a serious health problem world levels in the year 2011 there were 8.7 million new cases and 1.4 million people died from TB. To flatten the actions in combating TB in the primary care community health agent plays a very important role, as they besides working in the community where he lives is a mediator of knowledge, it is expected that this professional is able to identify through home visits with respiratory symptoms. Objectives: To study the perception that the ACS have on the risk of tuberculosis infection in their daily practice and analyze how they organize and structure their practice against that perception. Methodological: The study was divided into two phases the first goal and responds to the primer was chosen the Focus Group and the second phase that responds to the second objective was selected as a Participant Observation techniques for field work and Thematic Content Analysis as a technique to analyze data that consists of discovering the core meanings are topics which are units of meaning that are released naturally from a parsed text. Results: In the first phase of the study it was observed that the Community Health Agents realize the risks they are exposed, but often they do not know how to act in situations, specific, in the second phase indicate that the risk is not present at all in life and in their work. Conclusion: The PACS is presented by the Ministry of Health as a health strategy to flatten actions in TB control, this study found that the risk ACS realizes that this exposed, but that risk is not always presents in their lives, they often minimize the risks thinking that nothing happens or happened to them.